2020
DOI: 10.31234/osf.io/kd2cz
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Treating Tourette Together: An Agenda for Patient-Centered Research Focused on Comprehensive Behavior Therapy for Tics

Abstract: After the Summit, we organized this input into 4 Key Research Areas that described the general types of research that attendees felt passionately about.Here, we list these domains, as well as specific Research Questions within each domain. Even though we number these below, each is considered equally important (for example, #3 isn't a lower priority than #1). Key Research Domains and Sample Questions Domain 1: Increasing Access to CBIT Representative research questions include:1. Children spend a lot of time i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
0
0
Order By: Relevance
“…Treatment guidelines published by the American Academy of Neurology (AAN) (Pringsheim et al 2019) Conelea and colleagues initiated a project involving researchers, clinicians, patients, and families with the aim to identify future priorities for research of BT for TS/CTD (Conelea et al 2024). Key research domains were identified through anonymous community surveys.…”
Section: Psychological Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment guidelines published by the American Academy of Neurology (AAN) (Pringsheim et al 2019) Conelea and colleagues initiated a project involving researchers, clinicians, patients, and families with the aim to identify future priorities for research of BT for TS/CTD (Conelea et al 2024). Key research domains were identified through anonymous community surveys.…”
Section: Psychological Interventionsmentioning
confidence: 99%
“…Another domain identified by the survey conducted by Conelea and colleagues was ways to improve treatment outcomes, which in turn may be linked to identifying the underlying working mechanisms of BT (Conelea et al 2024). A proposed working mechanism of BT is within-session habituation to aversive sensations preceding tic occurrence (i.e., premonitory urges).…”
Section: Psychological Interventionsmentioning
confidence: 99%